Magnetic separation of paramagnetic ions from initially homogeneous solutions - Yang, X; Tschulik, K; Uhlemann, M; Odenbach, S; Eckert, K (2014)
© 1965-2012 IEEE. The concentration change in an initially homogeneous paramagnetic solution is studied interferometrically upon applying sufficiently strong inhomogeneous magnetic fields. For this purpose, five different magnetic field configurations are analyzed. Clear evidence is provided that an enrichment of paramagnetic ions occurs in the field gradient. In particular, we show that the shape of this enrichment layer maps the spatial distribution of the magnetic field gradient force.